Fatigue crack propagation prediction of a pressure vessel mild steel based on a strain energy density model - PJ. Huffman; J. Ferreira; J A F O. Correia; A M P. De Jesu; G. Lesiuk; F. Berto; A. Fernndez-Canteli; G. Glinka (Fracture and Structural Integrity)
Fatigue crack growth (FCG) rates have traditionally been formulated from fracture mechanics, whereas fatigue crack initiation has been empirically described using stress-life or strain-life methods. More recently, there has been efforts towards the use of the local stress-strain and similitude concepts to formulate fatigue crack growth rates. A new model has been developed which derives stress-life, strain-life and fatigue crack growth rates from strain energy density concepts. This new model has the advantage to predict an intrinsic stress ratio effect of the form sar=(samp)?(smax )(1-?), which is dependent on the cyclic stress-strain behaviour of the material. This new fatigue crack propagation model was proposed by Huffman based on Walkerlike strain-life relation. This model is applied to FCG data available for the P355NL1 pressure vessel steel. A comparison of the experimental results and the Huffman crack propagation model is made.